Implementation of Good University Governance in Services for Students with Disabilities at Islamic Universities: A Literature Review - Zaitun Qamariah; Ibnu Elmi A.S. Pelu (Mudir: Jurnal Manajemen Pendidikan, 2025)
Inclusive higher education is a fundamental right for students with disabilities. Although various regulations have promoted inclusivity in Islamic higher education institutions in Indonesia, implementation remains challenging. This study aims to analyse the challenges and strategies for implementing inclusive education in State Islamic Higher Education Institutions (PTKIN) through the perspectives of Good University Governance (GUG) and Inclusive Service Management. The research employs a library research method with a qualitative approach to examine policies, challenges, and best practices. The findings indicate that the main obstacles include inaccessible infrastructure, limited inclusive policies, and inadequate teacher training. The implementation of GUG based on transparency and accountability has proven to enhance the effectiveness of inclusive policies. In conclusion, integrating GUG and Inclusive Service Management is an effective strategy for creating a more inclusive and equitable university environment.